PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP MINAT BELAJAR SISWA KELAS IV DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DI SD NEGERI 29 RANTAU BATU PASAR - Bagindo, Intan Suri; Dwiana, Ari Aprilia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The application of audio-visual learning media in elementary schools, especially in Pancasila Education subjects, has an impact not only on the effectiveness of understanding the material but also on improving students' social skills. This study aims to determine the influence of audio-visual learning media on the learning interest of grade IV students in Pancasila Education subjects. The background of this research is based on the low interest of students in learning Pancasila Education material which is theoretical and contextual. The method used in this study is Kuantitative with a quasi-experimental approach, which involves two classes, namely the experimental class that uses audio-visual media and the control class that uses conventional methods. The data collection technique is by learning interest questionnaires, observation and documentation. The results of the study show that the use of audio-visual learning media significantly increases students' interest in learning, which can be seen from the increased enthusiasm, attention and activeness of students during the learning process. The conclusion of this study is that audio visual learning media has a positive effect on increasing students' learning interest in Pancasila Education subjects.